Kajian Konseptual E-Modul Berbasis Discovery Learning untuk Meningkatkan Hasil Belajar - Agapau, Julianti Dian Lestari; Ningsih, Kurnia; Titin (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
E-modules based on discovery learning are electronic teaching materials containing videos, images and audio which are arranged systematically and include the stages or syntax of the discovery learning model, namely stimulus, problem identification, data processing, proof and conclusions. The concepts obtained in this discovery learning-based e-module are not shown final form, but rather students recognize and prove existing concepts so that they gain meaningful knowledge and long-lasting memories. Therefore, this teaching material requires student activity because discovery learning-based e-modules encourage students to learn independently. The teacher only acts as a facilitator or accompanies students. This research aims to determine the effectiveness of discovery learning-based e-modules in improving student learning outcomes. The research method used is literature study, where the data obtained is recorded, analyzed and concluded. The results of the study show that e-modules based on discovery learning are able to improve student learning outcomes.